2008
DOI: 10.1128/iai.01376-07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Isoprenoid Biosynthesis Pathways in Listeria monocytogenes Reveals a Role for the Alternative 2-C-Methyl- d -Erythritol 4-Phosphate Pathway in Murine Infection

Abstract: Most bacteria synthesize isoprenoids through one of two essential pathways which provide the basic building block, isopentyl diphosphate (IPP): either the classical mevalonate pathway or the alternative non-mevalonate 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway. However, postgenomic analyses of the Listeria monocytogenes genome revealed that this pathogen possesses the genetic capacity to produce the complete set of enzymes involved in both pathways. The nonpathogenic species Listeria innocua naturally l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
3
26
1
Order By: Relevance
“…We then sought to determine whether removing gcpE from our attenuated Listeria strain would further impact bacterial replication and immunogenicity. This question needs to be addressed, as a study demonstrates that the HMBPP/MEP pathway influences virulence for a WT Listeria strain [31]. We confirmed that gcpE deletion in a WT strain of Listeria (10403S) resulted in decreases in bacterial loads in spleen and liver following i.v.…”
Section: A Deletion Of Gcpe-encoding Enzyme For Producing Hmbpp In Thsupporting
confidence: 69%
See 3 more Smart Citations
“…We then sought to determine whether removing gcpE from our attenuated Listeria strain would further impact bacterial replication and immunogenicity. This question needs to be addressed, as a study demonstrates that the HMBPP/MEP pathway influences virulence for a WT Listeria strain [31]. We confirmed that gcpE deletion in a WT strain of Listeria (10403S) resulted in decreases in bacterial loads in spleen and liver following i.v.…”
Section: A Deletion Of Gcpe-encoding Enzyme For Producing Hmbpp In Thsupporting
confidence: 69%
“…Our study represents the first in vivo comparative investigation dissecting importance of HMBPP/IPP coproduction versus IPP production for eliciting V␥2V␦2 T cell expansion, differentiation, and memory formation during intracellular bacterial immunization. A number of pathogens, including most detrimental ones that cause TB, cholera, diphtheria, and plague, indeed carry the MEP pathway for HMBPP/IPP coproduction without an additional mevalonate IPP pathway [3,31] and activate/expand V␥2V␦2 T cells. Our primate model and listerial mutant system provide a unique opportunity to document whether and how HMBPP deficiency during immunization with HMBPP-producing bacteria impacts in vivo responses of V␥2V␦2 T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of [4Fe-4S] cluster biosynthesis for these two enzymes was underlined by the recent demonstration that E. coli can survive a knockout of both Fe-S assembly systems, ISC and SUF, as long as mevalonate and the lower genes of the mevalonate pathway are provided to ensure a supply of IPP and DMAPP (Tanaka et al, 2016). It’s also interesting to note that while pathogenic strains of Listeria monocytogenes maintain a full DXP pathway as well as a mevalonate pathway, its non-pathogenic relative Listeria innocua has specifically lost the genes encoding IspG and IspH, suggesting that these two [4Fe-4S] enzymes may constitute a high metabolic or physiological burden (Begley et al, 2008). …”
Section: Discussionmentioning
confidence: 99%